Understanding the Archaeological Record: Reconstructing a Warp-Weighted Loom - Tena Karavidović; Tajana Sekelj Ivančan (EXARC Journal)
The paper deals with a reconstruction of a warp-weighted loom based on a rare find of 36 in situ loom weights in an object interpreted as a weaving hut at an archaeological site Virje-Sušine in Northern Croatia dated in late Iron Age (La Tène C period, 2/2 3rd – 2/2 2nd century BC). The case study includes a theoretical framework for warping based on defining functional elements of different types of loom-weights (thread density, what yarn to use) and study of wear marks on weights which defined the usage. A series of experiments were carried out to define possible distributions of weights in the same loom setup, characteristics of woven cloth, and wooden loom construction. The linear distribution of different types of loom-weights and weights with incised signs within the optimal loom setup showed some regularities which can be connected with technological requirement of producing cloth on a warp-weighted loom but also with design/pattern making.